2008
DOI: 10.1002/chem.200801120
|View full text |Cite
|
Sign up to set email alerts
|

Complete Direct and Reverse Optically Induced Valence Tautomeric Interconversion in a Cobalt–Dioxolene Complex

Abstract: A solvent tune: The crystallization solvent affects the temperature and light dependence of the valence tautomeric behaviour of a 1:1 Co–dioxolene compound, thus offering a new possibility of tuning its charge distribution (see figure). This approach paves the way for the development of molecular magnetic materials whose properties may be controlled by chemical means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
97
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 40 publications
13
97
1
3
Order By: Relevance
“…It has recently been shown that the isotrop- Figure 1. Molecular structure of 1, derived by partial resolution of XRD data, [20] highlighting the octahedral coordination sphere of the Co ion. The presence of toluene in the lattice plays a determining role in the entropyand optically-driven intramolecular ET process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has recently been shown that the isotrop- Figure 1. Molecular structure of 1, derived by partial resolution of XRD data, [20] highlighting the octahedral coordination sphere of the Co ion. The presence of toluene in the lattice plays a determining role in the entropyand optically-driven intramolecular ET process.…”
Section: Resultsmentioning
confidence: 99%
“…[20] To get the appropriate mechanical stability, the microcrystalline powder sample was mixed with boron nitride in a 1:1 weight/ weight ratio and pelleted under a pressure of 1 ton.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 It gives a nice opportunity to look into the interrelation between the physics of phase transition and that of nonlinear dynamics because these are the same cooperative interactions, that govern the stability of macroscopic states both at thermal equilibrium and out of equilibrium. The approach presented here, balancing the intra and intermolecular aspects involved during both thermal and photoconversions, can also be used in other bistable magnetic systems such as polycyanometallate derivatives, [9][10][11] valence tautomeric complexes, 12,13 ligand isomerization effects, 14 etc. The spin-state switching can occur in molecular solids 5 made of a metal ion located in a nearly octahedral ligand molecular field.…”
Section: Introductionmentioning
confidence: 99%